The transmission of foreign monetary policy shocks into the United States through foreign banks - Temesvary, Judit (Journal of Financial Stability, 2018)
This paper examines how the lending of all foreign banks (branches and subsidiaries) in the US responds to foreign monetary policy actions in their parents’ home countries. Using a rarely studied bank-level dataset covering US-based foreign bank offices over the 1997–2014 period, I find strong evidence of a bank lending channel of inward monetary policy transmission: In response to home country monetary tightening, foreign banks with less access to liquid funds reduce their business lending in the US substantially more than foreign banks with more funding access. This inward transmission is strongest for the pre-crisis period, and for foreign banks originating from Europe.